Problems Faced By Secondary School Teachers During Teaching In Multi Religious Classrooms - Muhammad Sakhawat Zia; Sidra Jabeen; Maryam Siddiqa; Badar Zaman (Cita konsultindo, 2023)
Religion is a greatest source of development. A society can be changed through rules and values of any religion. It is such a tool which helps to bring change not only in the society but in individual also. It provides positive thinking in a man. It develops sensibility so that a man can understand all the complications of life and be able to solve all the problem. To teach the society a teacher plays a vital role without the effort of the teachers, the schools, administrators, experts and parents cannot adopt change and bring improvement in student’s academic performance alone. This research study was explored the Problems faced by secondary school teachers during teaching in multireligious classrooms. This study was carried out in Nankana Sahib, Punjab Pakistan. The sample of this study was based on 100 boys Muslim’s students and 100 Non-Muslim Students of the boy’s school’s by using random sampling technique. A random sampling technique was carried out from the population. The sample of this study was based on 100 boys Muslim’s students and 100 Non-Muslim Students of the boy’s school’s by using random sampling technique. It was found that teachers face several problems in teaching due the different religion of students. It was suggested that The needs of professional training should be set for developing critical thinking among teachers due to facing the students of any religion. The needs of professional training should be set for helping the teacher to encounter difficulties about implementing in multi religious classroom.